Management Strategy for marine turtle conservation on the Caribbean Coast of Nicaragua / Cynthia J. Lagueux y otros - Lagueux, Cynthia J. Cambell, Cathi L. (2005)
It is increasingly recognized that maintaining biodiversity is of fundamental importance toward sustaining human livelihoods. One of the major assets of the region identified as.